The lost and found girl - Yates, Maisey (HQN, 2022)
"Ruby McKee is a miracle. Found abandoned on a bridge as a newborn baby by the McKee sisters, she's become the unofficial mascot of Pear Blossom, Oregon, a symbol of hope in the wake of a devastating loss. Ruby has lived a charmed life, and when she returns home after traveling abroad, she's expecting to settle into that charm. But an encounter with the town's black sheep makes her question the truth about her mysterious past. Dahlia McKee knows it's not right to resent Ruby for being special. But uncovering the truth about Ruby's origins could allow Dahlia to carve her own place in Pear Blossom history. Recently widowed Lydia McKee has enough on her plate without taking on Ruby's quest for answers. Especially when her husband's best friend, Chase, is beginning to become a complication she doesn't want or need. Marianne Martin is glad her youngest sister is back in town, but it's hard to support Ruby's crusade when her own life is imploding. When the quest for the truth about Ruby's origins uncovers a devastating secret, will the McKee sisters fall apart or band together?" -- Jacket flap